The Performance of Household-Scale Horizontal Flow Constructed Wetland (HFCW) Unit for Treating Greywater - Suleman, Iriani Putri; Sofiyah, Evi Siti; Ridhosari, Betanti (Universitas Diponegoro, 2024)
Horizontal flow constructed wetland (HFCW) is a method mimicking natural processes in which plantations are used to treat wastewater. This method demonstrates superior efficacy in the removal of organic pollutants and total nitrogen. Furthermore, it offers the advantage of reduced operational and maintenance expenses. This research employs a household-scale HFCW unit, utilizing water hyacinths (Eichornia crassipes) to treat greywater from a single house. The study aims to assess the HFCW unit's performance in treating greywater at a household scale, with effluent quality compared against Minister of Environment and Forestry Regulation (Regulation Number 68/2016 on Domestic Wastewater Quality Standard) using testing methods in accordance with the Indonesian National Standards (SNI). The results indicate that the HFCW unit removal efficiencies after two days retention time are: BOD5 (74%-93%), COD (47%-80%), TSS (55%-97%), oil and grease (50%-94%), and ammonia (46%-99%). After three days, the unit generally demonstrates improved performance, which are: BOD5 (67%-96%), COD (57%-91%), TSS (51%-97%), oil and grease (11%-99%), and ammonia (35%-99%). Overall, the effluent quality meets government standards for both two- and three-days retention time, establishing the HFCW unit as an effective household-scale greywater treatment solution.